Spatial and temporal multidimensional poverty in Nigeria - Olu Ajakaiye; Afeikhena T. Jerome; Olanrewaju Olaniyan; Kristi Mahrt; Olufunke A. Alaba (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Nigeria has recorded impressive growth in the last decade, yet the impact of this growth on poverty reduction remains unclear. This paper appraises spatial and temporal non-monetary multidimensional poverty in Nigeria using the first-order dominance approach. It examines five welfare indicators: education, water, sanitation, shelter, and energy. While the analysis is sensitive to indicator definitions, the overall results are robust and lend support to the view that poverty reduction has not kept pace with the rapid economic growth attained in the last decade. The analyses indicate that regional inequalities remain profound with huge disparities between the urban and rural sectors as well as between the far south and the rest of the country.
Keywords: I30; I31; I32; O12; 330; Nigeria; economic growth; poverty reduction; first-order dominance approach; multidimensional welfare